Zero-waste preparation of supramolecular hydrogels and films comprising tannic acid and ultra-high-molecular-weight polyethylene oxide - Yuika Goto; Airi Obata; Masamichi Inoue; Toru Taharabaru; Takuya Kihara; Risako Onodera; Daisuke Iohara; Makoto Takafuji; Keiichi Motoyama; Taishi Higashi (Results in Materials, 2023)
Recently, tannic acid (TA) has been attracting attention as a component for supramolecular hydrogels. In fact, TA was reported to form viscous hydrogels with polyethylene oxide (PEO) (∼10 kDa), a typical macromolecule; however, little is known about hydrogels consisting of TA with ultra-high-molecular-weight (UHMW) PEO (≥100 kDa). In this study, TA/PEO hydrogels containing PEO of various molecular weights are prepared to investigate the effects of the molecular weight of PEO on the structure and characteristic physical properties of TA/PEO hydrogels. Interestingly, UHMW PEOs (≥100 kDa) formed stretchable hydrogel aggregates (TaPeO Gel), which were completely different from existing viscous TA/PEO gels (∼10 kDa). The mechanical properties of the TaPeO Gel (500 kDa) include high elongation, strong adhesive ability, and anti-swelling properties. In addition, the TaPeO Gel dried at 40 °C for 8 days was a lightweight and rigid material that exhibited shape memory and self-healing properties. Furthermore, a highly stretchable film (TaPeO Film) was obtained during the preparation of the TaPeO Gel by drying the unwanted supernatant from the TA/PEO mixture. These results suggest that advanced supramolecular gels and films can be prepared simultaneously from TA and UHMW PEO in a zero-waste process.